Analysis of the Influence of Library Facilities on Visiting Decisions at Maranatha Christian University - Neneng Sayidah; Betarum Damaris (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Purpose Research. This study aims to analyze the influence of library facility usage on the visiting decisions of the academic community at Universitas Kristen Maranatha. Amidst digital transformation, the library's role as an intellectual hub is vital, yet relatively low visit data presents a paradox. This research is important for providing an empirical analysis of the relationship between facility usage and visiting interest. Research Method. Using a quantitative correlational approach, primary data were obtained through an online questionnaire from 125 respondents selected using a simple random sampling technique. Direct observation and literature studies were also conducted as secondary data. Analysis Data. The data were analyzed using IBM SPSS Statistics software. Validity (Pearson Product Moment) and reliability (Alpha Cronbach) tests were conducted to ensure the research instrument was reliable. Hypothesis testing was performed using Spearman's rank order correlation analysis at a significance level of 0.05. Results. : A significant relationship was found between the use of library facilities and the visiting decision, with a correlation coefficient of 0.780, which is classified as "high". Visitors gave a very positive perception of the facilities, especially the comfort of the rooms. Conclusions. The quality and completeness of facilities have a strong and significant influence on a person's decision to visit the library, indicating that investment in infrastructure and resources is an effective strategic step to increase visits. Keywords: visiting decision; facilities; library; maranatha christian university